A qualitative study of the needs of parents of handicapped pre-schoolers attending a special school - Brümmer, Laetitia (School of Education, 2016)
This thesis is an assessment of the needs of parents and families of handicapped preschoolers attending a special school. The focus is on school related needs. An assessment of these needs could concentrate on child related needs or include needs relating to parent and family well-being. In chapter I this question is debated in light of literature on early intervention history and practice in the USA. The reciprocal interaction of handicap and family is seen to be important. This necessitates a family systems approach with a wider interpretation of family needs. In Chapter II background is given to the application of family systems theory to families with handicapped children. The importance of an ecosystemic viewpoint to special educational studies is explained and the role of support systems investigated. Theories pertaining to the processes of stress, coping and adaptation are introduced. The special contributions of authors such as Bronfenbrenner (1976 and 1977); Dunst (1985); Kazak (1987); McCubbin and Patterson (1983) and Turnbull and Turnbull (1986) are mentioned in this chapter. Chapters III and IV then give an overview of the rich literature pertaining to families with handicapped young children and their special needs.